Cenários de aprendizagem integradora: experiências com as rodas de diálogo - Dojas, Júlia Bernardo (2008)
It is about the analysis under the Circles of Dialogue being conceived as strategies for integrator learning. The research brings the experience with Dialogue and other playful and artistic activities for the integral formation of students of Aldeia do Futuro. The Circles of Dialogue, as integrator learning strategies, were observed under the perspective of promoting connections, with oneself, with the others and the environment. The participants of the research are teenagers, between 14 and 20 years, inhabitants of the quarter of Americanópolis and region. The theory was structured by studies on the complexity and the concepts of integrator learning. In turn, agreeing with the process of learning construction surrounding harmonic and healthy, where the spontaneous expression is respected and the collective intelligence is stimulated